The Beginnings of National Politics An Interpretive History of the Continental Congress - Rakove, Jack N., 1947-; Project Muse; Project Muse. (Project Muse, 2019)
Despite a necessary preoccupation with the Revolutionary struggle, America's Continental Congress succeeded in establishing itself as a governing body with national--and international--authority. How the Congress acquired and maintained this power and how the delegates sought to resolve the complex theoretical problems that arose in forming a federal government are the issues confronted in Jack N. Rakove's searching reappraisal of Revolution-era politics. Avoiding the tendency to interpret the decisions of the Congress in terms of competing factions or conflicting ideologies, Rakove opts for a more pragmatic view. He reconstructs the political climate of the Revolutionary period, mapping out both the immediate problems confronting the Congress and the available alternatives as perceived by the delegates. He recreates a landscape littered with unfamiliar issues, intractable problems, unattractive choices, and partial solutions, all of which influenced congressional decisions on matters as prosaic as military logistics or as abstract as the definition of federalism.
part 1. Resistance and revolution : resistance without union, 1770-1774 -- The creation of a mandate -- The First Continental Congress -- War and politics, 1775-1776 -- Independence -- A lengthening war -- part 2. Confederation : confederation considered -- Confederation drafted -- The beginnings of national government -- Ambition and responsibility : an essay on revolutionary politics -- part 3. Crises : factional conflict and foreign policy -- A government without money -- The administration of Robert Morris -- part 4. Reform : union without power : the confederation in peacetime -- Toward the Philadelphia Convention.
Originally published: Baltimore, Maryland : Johns Hopkins University Press, 1982.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United States. -- Continental Congress; United States -- Politics and government -- 1783-1789.; United States -- Politics and government -- 1775-1783.; Electronic books; Electronic books